2015
DOI: 10.1371/journal.pone.0133397
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Transgenic Mouse with R124H Human TGFBI Mutation Associated with Granular Corneal Dystrophy Type 2

Abstract: PurposeTo investigate the phenotype and predisposing factors of a granular corneal dystrophy type 2 transgenic mouse model.MethodsHuman TGFBI cDNA with R124H mutation was used to make a transgenic mouse expressing human protein (TGFBIR124H mouse). Reverse transcription PCR (RT-PCR) was performed to analyze TGFBIR124H expression. A total of 226 mice including 23 homozygotes, 106 heterozygotes and 97 wild-type mice were examined for phenotype. Affected mice were also examined by histology, immunohistochemistry a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 21 publications
2
23
1
Order By: Relevance
“…In Tgfbi R124C/R124C mice, more than 70% of eyes developed corneal opacity by 40 weeks of age ( Table 1). The frequency of corneal opacity in our mutant mice was nearly four times greater than that in previously established mouse models 8 . On the other hand, no corneal opacity was observed in Tgfbi R124C/WT mice up to 20 weeks of age, and the frequency of corneal opacity by 40 weeks was lower than that in Tgfbi R124C/R124C mice.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In Tgfbi R124C/R124C mice, more than 70% of eyes developed corneal opacity by 40 weeks of age ( Table 1). The frequency of corneal opacity in our mutant mice was nearly four times greater than that in previously established mouse models 8 . On the other hand, no corneal opacity was observed in Tgfbi R124C/WT mice up to 20 weeks of age, and the frequency of corneal opacity by 40 weeks was lower than that in Tgfbi R124C/R124C mice.…”
Section: Discussioncontrasting
confidence: 56%
“…Establishing clinically relevant mouse models of TGFBI corneal dystrophy would be very helpful to understand the mechanisms or pathophysiology underlying corneal opacity. Two animal models of TGFBI corneal dystrophy have been established via introduction of human mutant TGFBI genes into mice 6,8 . However, these models were generated by artificial induction of human genetic mutations, and the frequency of corneal opacity observed was insufficient to explain the patient phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Yamazoe et al () reported a transgenic mouse model of GCD2 caused by the p.Arg124His variant, showing granular with or without lattice deposits in the center of the cornea. Histology was similar to that of human‐affected corneas.…”
Section: Tgfbi Expression Role and Pathology In The Eye Of Humans Amentioning
confidence: 99%
“…Histology was similar to that of human‐affected corneas. As not all transgenic animals had corneal opacities, the authors concluded that epigenetic and/or environmental factors could influence the phenotype in mice and humans (Yamazoe et al, ). As mentioned above, our p.Arg124Leu knock‐in animal failed to show any corneal deposits, either at the heterozygous or homozygous state (data not shown).…”
Section: Tgfbi Expression Role and Pathology In The Eye Of Humans Amentioning
confidence: 99%
“…There have been several previous attempts to generate a suitable transgenic animal model, either to knock-in or knock-out TGFBI gene, and to evaluate the pathologic role of the mutant protein [54][55][56] . All the generated animal models were not very successful to express the disease phenotype or in the survival of the animals.…”
Section: Discussionmentioning
confidence: 99%